Factors predicting 30‐day readmission after laparoscopic colorectal cancer surgery within an enhanced recovery programme. (July 2015) - Francis, N. K.; Mason, J.; Salib, E.; Allanby, L.; Messenger, D.; Allison, A. S.; Smart, N. J.; Ockrim, J. B.
Abstract Aim Hospital readmission within 30 days of surgery has become a marker of poor quality patient care. This study aimed to investigate factors predictive of 30‐day readmission after laparoscopic colorectal cancer surgery within an enhanced recovery after surgery (ERAS) programme. Method Consecutive patients undergoing laparoscopic surgery for colorectal cancer within an ERAS programme between 2002 and 2009 were included. Data were collected relating to patient demographics, neoadjuvant chemoradiotherapy, ERAS compliance, and operative and postoperative outcomes. A logistic regression model was used to identify factors associated with readmissions after adjusting for the potential effect of covariables simultaneously. Results In all, 268 cancer patients underwent laparoscopic colorectal surgery (108 rectal resections), of whom 34 (12.7%) were readmitted due most commonly to bowel obstruction (29%) and surgical site infection (18%). The use of neoadjuvant therapy (odds ratio 4.49, 95% CI 1.41–14.35; P = 0.011) and ERAS compliance above 93% (odds ratio 0.38, 95% CI 0.18–0.84; P = 0.016) were independent predictors of readmission. Conclusion Poor ERAS compliance and preoperative chemoradiotherapy were significant predictors of readmission following laparoscopic colorectal cancer surgery. Further research is required to expand the scope of ERAS beyond hospital discharge.